Control of Wind-Induced Vibration of Transmission Tower-Line System by Using a Spring Pendulum. (5th March 2015) - Zhang, Peng; Ren, Liang; Li, Hongnan; Jia, Ziguang; Jiang, Tao
Abstract : The high-voltage power transmission tower-line system, which is a high flexible structure, is very susceptible to the wind-induced vibrations. This paper proposes the utilization of the internal resonance feature of the spring pendulum to reduce the wind-induced vibration of a transmission tower. The kinetic expression of the spring pendulum system is obtained through Lagrangian equation. The condition of the internal resonance is verified to be λ  = 2, in which λ is the ratio of the spring mode frequency over the pendulum mode frequency. A 55 m tower in the Liaoning province is established in SAP2000 to numerically verify the effectiveness of the proposed device. The spring pendulum is modeled using Link element. The wind speed history is generated based on Kaimal spectrum using harmonic superposition method. Results show that, (1) compared with the suspended mass pendulum, the spring pendulum absorbs more energy and reduces the oscillation more effectively and (2) the vibration control performance of the proposed spring pendulum improves as the external wind load increases.